2005
DOI: 10.1369/jhc.4a6430.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Aneuploidy Frequency in the Developing and Adult Human Brain Revealed by an Interphase FISH Study

Abstract: and Institute of Pediatrics and Children's Surgery, Russian Ministry of Health, Moscow, Russia (SGV) S U M M A R Y Despite the lack of direct cytogenetic studies, the neuronal cells of the normal human brain have been postulated to contain normal (diploid) chromosomal complement. Direct proof of a chromosomal mutation presence leading to large-scale genomic alterations in neuronal cells has been missing in the human brain. Large-scale genomic variations due to chromosomal complement instability in developing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
138
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 11 publications
7
138
1
5
Order By: Relevance
“…1c, Table 1). The frequency of the aneuploid cells in the controls was within the range reported in adult human cells in culture [46,47]. In contrast, the SWCNT-treated SAEC had a level of aneuploidy that was as high as the effect that was observed in the vanadium pentoxidetreated positive control cells (Fig.…”
Section: Chromosome Numbersupporting
confidence: 75%
“…1c, Table 1). The frequency of the aneuploid cells in the controls was within the range reported in adult human cells in culture [46,47]. In contrast, the SWCNT-treated SAEC had a level of aneuploidy that was as high as the effect that was observed in the vanadium pentoxidetreated positive control cells (Fig.…”
Section: Chromosome Numbersupporting
confidence: 75%
“…This is in contrast to reports of genomic variations in other organs such as the reproductive system, the human brain or in hematological disorders [44,[53][54][55][56], where an association between aneuploidy and disease could be established [54,[56][57][58]. While it seems that all human tissues are affected by somatic genomic variations [59], albeit to a greatly varying extent, aneuploidy might be missed when present in rare cells [60,61]. This low frequency of genomic variants marks a demand for highly sensitive technologies-of-scale that offer the high throughput necessary to detect such rare events.…”
Section: Discussioncontrasting
confidence: 79%
“…Somatic mosaicism is well known to occur in normal germline cells as the process of meiotic recombination and in cells of the immune system within Ig and T-cell receptor genes as a result of V(D)J recombination that provides diversity in immune responses. Other studies have revealed age-related structural variation in human blood cells (14), aneuploidy and retrotransposition in the human brain (15,16), and aneuploidy in human preimplantation embryos (17). Evidence of copy number variation (CNV) in monozygotic twins (18) also reveals the presence of somatic mosaicism in tissues arising from the same zygote.…”
mentioning
confidence: 99%